Modelling the joint effects of body size and microclimate on heat budgets and foraging opportunities of ectotherms. Issue 3 (2nd December 2020) - Kearney, Michael R.; Porter, Warren P.; Huey, Raymond B.
Abstract: Body size affects the body temperature of an ectotherm by altering both heating rates and the microclimate experienced. These joint effects are rarely considered in the analyses of climatic constraints on ectotherms but nonetheless influence body temperatures and thus activity periods and foraging opportunities. Here we develop and test transient heat‐budget models that use height‐specific microclimatic forcing to compute the dynamics of size‐dependent body temperatures of ectotherms in sun and in shade. We incorporate a model of behavioural thermoregulation and use it to compute potential body temperatures and then to map these to ecologically relevant indices, including foraging opportunities and thermal constraints. To illustrate potential applications, we combine a microclimate model driven by a global climate database with the transient behavioural algorithm developed for lizards to explore how body size (10 and 1, 000 g) and size‐specific microclimate (at natural heights of 1 and 7.5 cm, respectively) interactively influence body temperatures and ecological indices at a warm, arid location in Australia in both spring and summer. To explore microclimatic effects, we contrast temperatures and indices for animals positioned at their natural versus reciprocal heights above the ground. Our simulations show that the behavioural and ecological consequences of size can be strongly biased when joint effects of body size and size‐imposed microclimate are ignored. For example, the two body sizes did not differ in total foraging time when compared at their natural heights, but did differ if compared at the same height, the direction of this difference reversing with the height at which they were compared. We show how computed foraging times can be translated to potential foraging radii from a central place (burrow or shade‐providing bush), thereby illustrating how body size can be physiologically translated into habitat connectivity as a function of different shade configurations, for example, as modified by fire regimes or shrub dieback. All functions are now integrated into the biophysical modelling r package Niche Map R and as a Shiny app, which should provide new insights and avenues for investigation into functional interactions between body size and habitat structure for ectotherms.